TAXATION OF FINANCIAL SECTOR AFTER THE CRISIS IN THE EUROPEAN UNION - Mara Eugenia-Ramona (Annals of the University of Oradea: Economic Science, 2012)
Taxation of financial sector is an important issue of the actual fiscal policy, especially after the economic crisis impact. By taxing the financial sector, it is intended taxation of financial transactions, and financial activities. European Union supports the taxation of the financial system and makes proposals in this regard. This paper tries to reveal the major aspects concerning the taxation of financial sector, both theoretical and empirical aspects. It will analyze the reasons which justify the application of such taxes, but also difficulties involved in practice. Another major objective of this paper is to examine the role of taxation in the financial sector as important regulatory instrument. This subject is debated in European Commission papers and by many economists. There are underlined the necessity of such tax, the impact and the economic efficiency. Our purpose is to identify if this kind of tax is good for our economy and what can be the impact from budgetary point of view. For finding this answers the paper realize a complex analysis of the types of taxes applied on financial sector in countries which already adopted this kind of taxes, like United Kingdom, Austria, Hungary, Cyprus. We believe that the financial sector should be charged, because was responsible in great measure the economic crisis impact. A potential tax applied to financial sector is considered as an important source of budget revenues. This article tries to explore the possible tax measures for financial sector according to the major principle of public finance –equity and efficiency. Special attention will be given to the need to implement financial sector taxation in Romania. In the years before the crisis banks and entire financial sector in Romania recorded significant profits. For this reason such tax is justified given that this sector is exempt from VAT. Applying such a tax would reduce the budget deficit and on the long term will reduce the public debt.